The Romanian Filmmaker’s Union. Between Ambiguous Past and Uncertain Future - Popescu, Alina (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
The Romanian Filmmakers’ Union is one of today’s largest cinematographic professional organisations inherited from the Communist past. This study looks at this specific form of institutionalising the activity of Romanian filmmakers from the perspective of its intermediary role between Party directives and divergent personal interests. The collapse of the regime made visible explosive tensions generated by this ambivalent institutional identity. It is therefore interesting to examine the consequences this organisation had on filmmakers’ status before and in the aftermath of the regime change. By using ethnographic methods, the article contributes to an understanding of the role the Union played in reconfiguring the professional community after 1989, especially after the coming of age of a generation of filmmakers who created new professional worlds that challenged the idea of ‘creative collectivity’.